An overview of correlation and regression methods in medical research – An ophthalmologic perspective - N Sreekumaran Nair; Sachit Ganapathy (Kerala Journal of Ophthalmology, 2023)
Correlation and regression are two commonly used statistical techniques in modelling medical data. It s essential for clinicians to understand the methodology of these techniques in general and their implications in clinical area of expertise. This article provides an overview on correlation and regression methods from an ophthalmologic perspective.